2022
DOI: 10.1038/s41598-022-12835-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics utilization to differentiate nonfunctional adenoma in essential hypertension and functional adenoma in primary aldosteronism

Abstract: We performed the present study to investigate the role of computed tomography (CT) radiomics in differentiating nonfunctional adenoma and aldosterone-producing adenoma (APA) and outcome prediction in patients with clinically suspected primary aldosteronism (PA). This study included 60 patients diagnosed with essential hypertension (EH) with nonfunctional adenoma on CT and 91 patients with unilateral surgically proven APA. Each whole nodule on unenhanced and venous phase CT images was segmented manually and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Among the baseline clinical variables, age, Time, SBP, DBP, potassium level, and Radscore significantly differed between the APA and NAA groups. The differences in age and potassium level were consistent with the findings reported by Chen and Bioletto et al, wherein the patients in the APA group were younger and had lower potassium concentrations [16,23]. However, in the current study, patients with normal baseline blood pressure were included because of the possibility of subclinical PA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among the baseline clinical variables, age, Time, SBP, DBP, potassium level, and Radscore significantly differed between the APA and NAA groups. The differences in age and potassium level were consistent with the findings reported by Chen and Bioletto et al, wherein the patients in the APA group were younger and had lower potassium concentrations [16,23]. However, in the current study, patients with normal baseline blood pressure were included because of the possibility of subclinical PA.…”
Section: Discussionsupporting
confidence: 88%
“…Radiomics has the ability to predict adrenocortical carcinomas, metastatic carcinomas, pheochromocytomas, and APAs by quantitatively extracting the features of adrenal lesions before surgery [12][13][14][15]. One study reported that contrastenhanced CT (CECT)-based radiomics can be used to identify non-functioning adrenal adenomas (NAAs) in patients with EH and APAs in patients with PA [16]. However, the study only included patients with EH with NAA because some subclinical PA patients have APA tumors, but the clinical manifestations are normal; that is, there are no or only mild symptoms of hypertension and hypokalemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, texture analysis was used for differentiating malignant from benign adrenal tumors [ 21 ]. Furthermore, Chen et al [ 28 ] and He et al [ 29 ] used radiomics signature and nomogram to confirm the risk of functional adenoma. Moreover, radiomics can be an effective medical approach for predicting subclinical pheochromocytoma from lipid-poor adenoma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, texture analysis was used for differentiating malignant from benign adrenal tumors [21]. Furthermore, Chen et al [27] and He et al [28] used radiomics signature and nomogram to con rm the risk of functional adenoma. Moreover, radiomics can be an effective medical approach for predicting subclinical pheochromocytoma from lipid-poor adenoma [22].…”
Section: Discussionmentioning
confidence: 99%